Origin of Crime and Methods of Research (Archives of Criminology, 2008)
The aim of the article by Leon Tyszkiewicz is to prove and demonstrate the role of the study of criminogenesis in the research on crime. The author defines criminogenesis and points out that in the past, its use in criminological researchwas ignored, especially by representatives of the positivistic trend. The research on criminogenesis has been developed mainly by humanistic criminology, which, based on moderate indeterminism, paid more attention to a person’s free will and the decision-making process that culminates in committing a crime. In his article, Tyszkiewicz refers to a paper delivered by a Belgian criminologist Etienne de Greeff, who in 1950 during the Second International Congress of Criminology in Paris was the first to stress the role of criminogenesis. The author suggests that the reasons for the increasing value of this method are that some criminologists are weary of quantitative research and do not use individual research methods enough, thus they treat criminals as statistical tables without their own unique histories, or base their research on weak statistical correlations. The author also argues that criminology should make more use of the advances of psychology, as this very field focusses on the motivations of human actions, which may be directly related to criminogenesis. Further in the article, Tyszkiewicz conducts an in-depth analysis of the methods for studying criminogenesis and distinguishes the following approaches: analytical, synthesizing, life history research, biographical method, and research into the decision-making process of criminals. The author looks at the individual methods, pointing out their strengths and weaknesses, and provides examples of research in which they were used. Tyszkiewicz further implies that criminogenesis is closely related to the science of social pathologies, pathogenesis. The article also mentions Polish criminologists who dealt with pathogenesis in their research, such as Batawia, Jasiński, Kołakowska-Przełomiec, Ostrihanska, Siemaszko, or Wójcik. In the conclusion of the text, the author stresses that although it would be necessary to decide which of the proposed methods of studying criminogenesis could be the most appropriate, one should not indicate any in order to maintain the necessary freedom of research. The author leaves it up to criminologists to choose the best method for studying the individual history of each person, stressing that it is not an easy task since science always tends to generalise to some extent.